Translation Errors in Serbian Legal Regulations and Their Impact on Text Interpretation and Law Application - Jovanović, Vojislav (NBP. Nauka, bezbednosti, policija, 2025)
Law, in addition to government, is the main element of every state, and it is woven from a whole set of legal regulations. Language is the main tool for expressing the legal content of regulations. Proper application of the regulation and understanding of the will of the person who made the regulation primarily implies linguistic interpretation and understanding of the content of the regulation. It is an axiom of every national legal certainty. On the other hand, in modern processes of globalization and regionalization of interstate relations, the issue of mutual harmonization of national legislations is gaining importance. The condition for successful harmonization is the adequate implementation of international and regional legal standards in the internal legal orders of individual countries, and the condition for adequate implementation is the correct and accurate translation of the legal regulations that are being implemented. Namely, adequate implementation and application of a legal regulation, written in a foreign language, first requires a linguistic understanding of that regulation, which is the essence of the normative interpretation of law, and errors that may occur in the process of implementing inevitably lead to misinterpretation, misunderstanding and misapplication of regulations. This further leads to legal uncertainty, legal disputes and irreversible losses of time and resources in resolving these disputes. The aim of this paper is to point out some of the errors in the translation of a legal text in order to make a modest contribution to translation practice in translation from English into Serbian.